A study on the Exchange Rate Pass-Through to consumer prices in Malta - Glenn Abela; Noel Rapa (Central Bank of Malta, 2021)
Exchange Rate Pass-Through (ERPT), commonly defined as the extent to which exchange rate changes are reflected in the price levels of an economy, has important implications in a number of policy-relevant areas. Despite this, estimates of ERPT in the Maltese economy are scarce and do not take into account changes in the monetary regime pertaining to the adoption of the euro. In this paper, we use local projections (LP) to estimate linear and non-linear ERPT to consumer prices in Malta after its accession to the European Monetary Union. In line with literature, results point at incomplete ERPT to headline consumer prices, peaking at around 20% by the end of the first year after the exchange rate shock. ERPT to overall HICP inflation seems to be largely driven by the goods component while ERPT to services prices is largely insignificant across the horizon considered. Allowing for non-linearities, we find evidence of asymmetric pass-through with larger changes to as well as depreciations in the nominal effective exchange rate being consistent with larger pass-through estimates.
Keywords: E31; F31; 330; Exchange Rate Pass-Through; Inflation; Local Projections; Impulse Response Functions; Non-Linearities